LEMBAGA PENDIDIKAN SAINS DAN ‎TEKNOLOGI PADA MASA KLASIK ISLAM - Sihaloho ‎, Wardani (UIN Sumatera Utara Medan, 2020)
The educational institutions of science and technology during the Islamic Classical period played a crucial role in the development of knowledge and technology that influenced both the Western and Eastern worlds. During this era, institutions like the Bayt al-Hikma (House of Wisdom) in Baghdad, along with madrasahs across the Islamic realm, became centers for scholarly research, translation, and innovation. Muslim scholars such as al-Khwarizmi, al-Razi, and Ibn Sina made significant contributions to mathematics, astronomy, medicine, and physics. These institutions not only taught religious sciences but also advanced scientific and technological fields, driving the progress of civilization. This study aims to analyze the structure, objectives, and impact of these educational institutions in the context of intellectual development and technological application during the period, and their lasting contributions to the modern world.